Environmental life cycle assessment as a tool for identification and assessment of environmental aspects in environmental management systems (EMS) part 1 methodology. - Lewandowska, Anna
Purpose The paper presents a discussion on the possibilities of using life cycle assessment (LCA) in identification and assessment of environmental aspects in environmental management systems based on the requirements of the international ISO14001 standard and the European Union EMAS regulation. Some modifications of LCA methodology are proposed in part 1, while the results of a review of environmental aspects for 36 organisations with implemented environmental management systems (EMS) are presented in part 2 of the article. Materials and methods The scope of the systems analysed in EMS and in LCA is different. This comes as the result of the fact that both ISO 14001 and EMAS are focused on an organisation contrary to ISO14040x, which are focused on a product life cycle. For the present work, this resulted in a need of adjusting the LCA methodology to EMS specificity, and vice versa. Some suggestions of such modifications are presented and discussed in the paper. Results A preliminary analysis was carried out on 36 organisations, which have EMS compliant wigh the ISO14001 or EMAS regulations. It has found a certain disproportion between input and output related environmental aspects included in most of the analysed registers. The probable reasons for such disproportion could be the fact that the output related environmental aspects are easier to manage by organisation and are often regulated by laws. Legal requirements are a significant criterion in the environmental aspects assessment. Discussion Based on the assessments carried out and the observations made, some conclusions have been drawn with regard to weaknesses and strengths and usefulness of LCA, as a result of a comparison to the traditional approaches used in EMS in the discussed area. LCA has evident advantages like : standardised methodology; possibility of inclusion of the quantitative information; presence of some methodological steps enabling the verification of the collected data; ability to generate of reproducible results. At the same time, the following potential weak points can be observed : a complexity of the procedure; higher time and cost requirements (especially related to an inventory phase); difficulties with assessing of environmental aspects with the qualitative character and these related to emergency situations; limitation related to the lack of relevant characterisation factors in the currently used LCIA methods. Conclusions LCA ought to be considered as a tool used for identification and assessment of environmental aspects in EMS. The listed limitations do not disqualify its suitability to be used. After certain simplifications, LCA seems to be a valuable alternative to the methodologies currently in use.
Keywords: Assessment; EMS; Environmental aspects; Identification; LCA